GOOTI PASTRIES: Online Cake Ordering System - Nur Athirah binti Abdul Razak; Robiah binti Hamzah (Journal of Computing Technologies and Creative Content, 2023)
This paper presents the development of Gooti Pastries' web-based Cake Ordering System. Objectives included analyzing requirements, designing a user-friendly interface, implementing efficient ordering and customization features, and conducting thorough testing. The system addresses manual order recording issues, repetitive bank detail sharing, order mix-ups, and difficulty visualizing custom cakes. Using Visual Studio Code, Laragon, MySQL, PHP, and Draw.io, the system was successfully developed and evaluated, resulting in improved cake ordering experiences. Recommendations focus on scalability, customization, and mobile compatibility to meet evolving customer needs. Gooti Pastries' system demonstrates efficient service delivery and adaptability in the digital age.